3D neutron tomography of steel reinforcement corrosion in cement-based composites. (20th February 2018) - Zhang, Peng; Liu, Zhaolin; Wang, Yu; Yang, Jinbo; Han, Songbai; Zhao, Tiejun
Highlights: Neutron tomography is an excellent NDT method to study steel corrosion in concrete. Spatial distribution of rebar corrosion in cementitious materials is visualized in 3D. Reinforcing steel starts corrosion from the bottom interface at the cracks. Multi-micro-cracked SHCC has higher resistance agains rebar corrosion than mortar. Abstract: Corrosion of steel reinforcement is one of the major durability problems for reinforced concrete structures. The steel corrosion in both ordinary mortar and strain hardening cementitious composites (SHCC) has been for the first time visualized by means of neutron tomography in three dimensions with high resolution. It has been found that the steel rebar starts corroding from the bottom interface between the steel and cementitious matrix. The corrosion products mainly exist around the cracks. Microcracking SHCC has higher resistance against steel rebar corrosion than cracked ordinary mortar.